Vaccine efficacy of a newly developed feed-based whole-cell polyvalent vaccine against vibriosis, streptococcosis and motile aeromonad septicemia in Asian seabass, Lates calcarifer - Mohamad, Aslah; Zamri-Saad, Mohd; Amal, Mohammad Noor Azmai; Al-saari, Nurhidayu (MDPI, 2021)
Multiple infections of several bacterial species are often observed under natural farm conditions. The infections would cause a much more significant loss compared to a single infectious agent. Vaccination is an essential strategy to prevent diseases in aquaculture, and oral vaccination has been proposed as a promising technique since it requires no handling of the fish and is easy to perform. This research attempts to develop and evaluate a potential feed-based polyvalent vaccine that can be used to treat multiple infections by Vibrios spp., Streptococcus agalactiae, and Aeromonas hydrophila, simultaneously. The oral polyvalent vaccine was prepared by mixing formalin-killed vaccine of V. harveyi, S. agalactiae, and A. hydrophila strains with commercial feed pellet, and palm oil as an adjuvant was added to improve their antigenicity. Thereafter, a vaccinated feed pellet was tested for feed quality analysis in terms of feed stability in water, proximate nutrient analysis, and palatability, safety, and growth performance using Asian seabass, Lates calcarifer as a fish host model. For immune response analysis, a total of 300 Asian seabass juveniles (15.8 ± 2.6 g) were divided into two groups in triplicate. Fish of group 1 were not vaccinated, while group 2 was vaccinated with the feed-based polyvalent vaccine. Vaccinations were carried out on days 0 and 14 with oral administration of the feed containing the bacterin at 5% body weight. Samples of serum for antibody and lysozyme study and the spleen and gut for gene expression analysis were collected at 7-day intervals for 6 weeks. Its efficacy in protecting fish was evaluated in aquarium challenge. Following vaccination by the polyvalent feed-based vaccine, IgM antibody levels showed a significant (p < 0.05) increase in serum against Vibrio harveyi, Aeromonas hydrophila, and Streptococcus agalactiae and reached the peak at week 3, 5, and 6, respectively. The high-stimulated antibody in the serum remained significantly higher than the control (p < 0.05) at the end of the 6 weeks vaccination trial. Not only that, but the serum lysozyme level was also increased significantly at week 4 (p < 0.05) as compared to the control treatment. The immune-related gene, dendritic cells, C3, Chemokine ligand 4 (CCL4), and major histocompatibility complex class I (MHC I) showed significantly higher expression (p < 0.05) after the fish were vaccinated with the oral vaccine. In the aquarium challenge, the vaccine provided a relative percentage survival of 75 ± 7.1%, 80 ± 0.0%, and 80 ± 0.0% after challenge with V. harveyi, A. hydrophila, and S. agalactiae, respectively. Combining our results demonstrate that the feed-based polyvalent vaccine could elicit significant innate and adaptive immunological responses, and this offers an opportunity for a comprehensive immunization against vibriosis, streptococcosis, and motile aeromonad septicemia in Asian seabass, Lates calcarifer. Nevertheless, this newly developed feed-based polyvalent vaccination can be a promising technique for effective and large-scale fish immunization in the aquaculture industry shortly.